DIGITAL TRANSFORMATION OF MADRASAH ALIYAH MANAGEMENT TO REALIZE THE QUALITY OF MADRASAH ALIYAH SUNANULHUDA - Hamdani, Mohammad Rusli; Rifaie, Muhammad Mukrim Faer; Rajan, Muhamad Sultan Al; Imron, Ali; Badrudin, Badrudin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Digitalization in this era has become a necessity. Where efficiency and sustainability have been popular lately. Today's institutions have undergone many transformations to achieve efficiency and quality in their management through digitalization. Including educational institutions which manage many things. Starting from institutional administration, educators, teaching staff, students, management of advice and infrastructure, etc. the method used is a qualitative data collection method using observation, interviews and documentation. The results obtained from this research have carried out digital transformation at MA Sunanulhuda, which includes 8 national education standards in order to realize quality madrasa education, including through the implementation of the Smart Digital Islamic Boarding School (PSD) application. Constraints and barriers to digital transformation at MA Sunanulhuda, financing, facilities and human resources educators who must match their competencies, be technologically literate, and be able to adapt to the learning process for the Gen Z generation